1971
DOI: 10.1002/app.1971.070150818
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of concentrated suspensions

Abstract: SynopsisThe dependence of the viscosities of highly concentrated suspensions on solids concentrations and particle size distributions is investigated by using an orifice viscometer. Based on the extensive amount of data on pertinent systems, an empirical equation which correlates the relative viscosities of suspensions (or relative moduli of filled polymeric materials) as a function of solids concentrations and particle size distributions is proposed. The equation has a constant which characterizes size distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
355
3
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 641 publications
(388 citation statements)
references
References 17 publications
19
355
3
1
Order By: Relevance
“…There have been various studies to illustrate the behavior of suspensions and suggested some viscosity models (Liu 2000;Krieger 1959;Chong and Baer 1971;Farris 1968). When taking into account the concrete, suggested viscosity models can be divided into two categories depending on the scale-level of constituents: unimodal suspension model and multimodal suspension model.…”
Section: Effects Of Particle Concentration and Particle Shape On Rheomentioning
confidence: 99%
See 2 more Smart Citations
“…There have been various studies to illustrate the behavior of suspensions and suggested some viscosity models (Liu 2000;Krieger 1959;Chong and Baer 1971;Farris 1968). When taking into account the concrete, suggested viscosity models can be divided into two categories depending on the scale-level of constituents: unimodal suspension model and multimodal suspension model.…”
Section: Effects Of Particle Concentration and Particle Shape On Rheomentioning
confidence: 99%
“…The last model was provided by Chong and Baer (1971) predicting the relative viscosity as a function of particle volume fraction and maximum packing fraction, which is defined as following:…”
Section: Effects Of Particle Concentration and Particle Shape On Rheomentioning
confidence: 99%
See 1 more Smart Citation
“…Among these factors, the dependence of suspension viscosity on the particle concentration is of great interest in the sediment field [2,3,19,20]. Experiments have been performed to study this relationship, and some models have been used to describe it [21][22][23][24][25][26]. However, a simple relationship may not exist because the particle in a suspending medium can Water 2017, 9, 474 2 of 14 be subject to hydrodynamic, Brownian, colloidal force and other effects, which are not easily modelled in a simple form [16,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…where η susp and η cont are the viscosities of the suspension system and that of the continuous phase, respectively; c is a constant; φ ∞ is usually between 60 % and 74 % related to close packing of the NaCl particles [18]. When φ v,disp is close to φ ∞ , η susp increases sharply and leads to very poor flowability of the mixture.…”
Section: Development Of the Sc/vv/pl Methodsmentioning
confidence: 99%